Molecular diversity and microsatellite polymorphism of modern maize hybrids - Mikić Sanja; Brbaklić Ljiljana; Stanisavljević Dušan; Kondić-Špika Ankica; Bekavac Goran; Mitrović Bojan; Trkulja Dragana; Mirosavljević Milan (Ratarstvo i Povrtarstvo, 2018)
The aim of this study was to estimate genetic diversity of 97 modern maize hybrids cultivated in Serbia with 12 microsatellite markers. In total, 89 alleles were detected, with the average of 7.4 alleles per locus. The polymorphic information content ranged from 0.42, for umc1792, to 0.81, for dupssr10, with an average of 0.64. The pairwise relatedness Ritland's values varied between 0.787 and -0.129. Eight markers were sufficient to differentiate hybrids with unique genotypes. A principal coordinate analysis distinguished early and late maturing groups of hybrids, although the observed differentiation between groups was low (Fst = 0.4%). Two markers, bnlg1556 and umc1075, contributed most to the discrimination between early and late genotypes. The values of parameters of molecular genetic diversity were higher in early than in late maturing hybrids, indicating broader genetic basis of the former. A high level of polymorphism of the markers indicates their suitability for fingerprinting.